Tracing site-specific isotopic signatures along a Blue Tit Cyanistes caeruleus food chain - Charmantier, Anne; Blondel, Jacques; Perret, Philippe; Harmelin-Vivien, Mireille (IBIS, 2014)
Food chains culminating with temperate insectivorous passerines are well described, yet whether trophic webs can be site-specific remains a largely unexplored question. In the case of site- or habitat-specificity of food webs, stable isotope signatures of bird feathers may enable assignment of unmarked individuals to a site or a habitat of origin. We address this question in landscapes that include contrasting forest habitat patches with either deciduous Downy Oak Quercus humilis or evergreen Holm Oak Quercus ilex as dominant tree species. First, we examine the spatial variation across habitats and sites in the stable isotope ratios of carbon (C-13) and nitrogen (N-15) along the oak leaf-Tortrix moth Tortrix viridana caterpillar-Blue Tit Cyanistes caeruleus food chain. Secondly, we assess whether the isotopic signatures allow for correct assignment of individual birds to their site or habitat of origin. At the scale of the landscape, stable isotope values enabled identification of the different components of the Blue Tit food chain: from oak leaves to Blue Tit nestlings and yearling birds. However, isotopic signatures were site-specific (i.e. geographical) more than habitat-specific (i.e. deciduous vs. evergreen oaks). Discriminant analyses correctly assigned 85% of nestlings and 83% of resident yearling birds, indicating a pronounced effect of site on Blue Tit feather isotopic signatures. We thereby demonstrate that isotopes reflect a stronger association of locally born birds to the local features of their habitat than that of un-ringed yearling birds, whose plumage may have grown while in a wider geographical area. This study provides evidence of site-specific isotopic signatures from oak leaves to Blue Tit feathers at a fine spatial scale.
The following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: environment heterogeneity; habitat-specific isotopic signature; natal dispersal; trophic ecology

Why do Corsican Blue Tits Cyanistes caeruleus ogliastrae not use nest boxes for roosting? - Dhondt, André a.; Blondel, Jacques; Perret, Philippe (Journal of Ornithology, 2009)
We compared winter roosting behaviour of Blue Tits Cyanistes caeruleus in the mainland of southern France and on the island of Corsica in small-holed nest boxes. While in southern France Blue Tits use nest boxes for roosting, Corsican Blue Tits do not. We suggest that this behaviour is innate because Corsican wild-caught as well as F1 and F2 birds born in captivity do not use nest boxes in aviaries even when kept adjacent to mainland tits that sleep in boxes. We suggest that the cost/beneﬁt balance differs between mainland France and Corsica: in Corsica, the costs of roosting in the canopy are less than in mainland France because (1) predators, e.g. owls, are rare in Corsica while abundant on the mainland, (2) the permanent evergreen foliage of the dominant tree in Corsica, the holm oak, could be preferred to nest boxes which are not risk-free, and (3) the costs of using cavities for roosting could be higher in Corsica because of increased mammal predator pressure and higher ectoparasite load than on the mainland.
Keywords: á parasitism á; Cyanistes caeruleus ogliastrae; cyanistes caeruleus ogliastrae á; Life-history trait; life-history trait á predation; Parasitism; Predation; Small-holed nest box

On humans and wildlife in Mediterranean islands - Blondel, Jacques (Journal of Biogeography, 2008)
Aim To investigate the effects of human-induced landscape changes in Mediterranean islands on the ecological and evolutionary responses of bird communities and populations. The combination of mass extinction of large mammals and massive deforestation by humans was hypothesized to produce new selection regimes to which organisms were likely to respond. Habitat selection and niche breadth have been investigated at the scale of species, and phenotypic variation at the scale of local populations. Location The study was carried out along habitat gradients and in habitat mosaics at different spatial scales on the island of Corsica and in areas of similar size and structure in continental France. Methods Two sets of gradients have been used for investigating habitat selection and niche breadth: gradients of altitude, and gradients of vegetation structure. Population studies focused on the blue tit, Cyanistes caeruleus. Large samples of breeding attempts by this species in 10 habitats provided detailed data on phenotypic variation of fitness-related traits both on Corsica and on the mainland. Results The extent of niche space used by birds differed substantially depending on which habitat gradient was considered. Many species have been found to contract their habitat niche along the elevation gradient on Corsica compared with the mainland, whereas all species in the vegetation gradient broadened their niche on the island. Breeding patterns of the blue tit differed considerably depending on whether they settle in deciduous oaks (Quercus humilis) or in evergreen sclerophyllous oaks (Quercus ilex). Phenotypic variation of breeding traits was much higher on the island, where more populations were correctly timed for the best breeding period than on the mainland, a pattern that is likely to result from lower dispersal of organisms on the island. Main conclusions The differences in observed niche breadth between the two series of habitat gradients is explained both by the species-specific ecology of the species and the human-induced environmental history of Corsica. Large-scale landscape changes provided new opportunities for island colonization by non-forest species, which are isolated as small, ‘fugitive’ local populations. In both gradients, forest species that are typical components of the Corsican bird fauna definitely expanded their niche and occupied a wider range of habitats on Corsica than on the mainland. At the population scale, landscapes included habitat patches with contrasted selection regimes, which resulted in high phenotypic variation for many fitness-related traits. Reduced dispersal of birds on the island resulted in a much higher degree of local differentiation on Corsica than on the mainland.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Blue tit; gene flow; habitat gradient; Human disturbance; insular syndrome; landscape changes; local differentiation; mass extinction; niche breadth; phenotypic variation

On humans and wildlife in Mediterranean islands - Blondel, Jacques (Journal of Biogeography, 2008)
Aim To investigate the effects of human-induced landscape changes in Mediterranean islands on the ecological and evolutionary responses of bird communities and populations. The combination of mass extinction of large mammals and massive deforestation by humans was hypothesized to produce new selection regimes to which organisms were likely to respond. Habitat selection and niche breadth have been investigated at the scale of species, and phenotypic variation at the scale of local populations. Location The study was carried out along habitat gradients and in habitat mosaics at different spatial scales on the island of Corsica and in areas of similar size and structure in continental France. Methods Two sets of gradients have been used for investigating habitat selection and niche breadth: gradients of altitude, and gradients of vegetation structure. Population studies focused on the blue tit, Cyanistes caeruleus. Large samples of breeding attempts by this species in 10 habitats provided detailed data on phenotypic variation of fitness-related traits both on Corsica and on the mainland. Results The extent of niche space used by birds differed substantially depending on which habitat gradient was considered. Many species have been found to contract their habitat niche along the elevation gradient on Corsica compared with the mainland, whereas all species in the vegetation gradient broadened their niche on the island. Breeding patterns of the blue tit differed considerably depending on whether they settle in deciduous oaks (Quercus humilis) or in evergreen sclerophyllous oaks (Quercus ilex). Phenotypic variation of breeding traits was much higher on the island, where more populations were correctly timed for the best breeding period than on the mainland, a pattern that is likely to result from lower dispersal of organisms on the island. Main conclusions The differences in observed niche breadth between the two series of habitat gradients is explained both by the species-specific ecology of the species and the human-induced environmental history of Corsica. Large-scale landscape changes provided new opportunities for island colonization by non-forest species, which are isolated as small, ‘fugitive’ local populations. In both gradients, forest species that are typical components of the Corsican bird fauna definitely expanded their niche and occupied a wider range of habitats on Corsica than on the mainland. At the population scale, landscapes included habitat patches with contrasted selection regimes, which resulted in high phenotypic variation for many fitness-related traits. Reduced dispersal of birds on the island resulted in a much higher degree of local differentiation on Corsica than on the mainland.
Keywords: Blue tit; gene flow; habitat gradient; Human disturbance; insular syndrome; landscape changes; local differentiation; mass extinction; niche breadth; phenotypic variation

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM.; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC.; Blondel, Jacques; Thomas, DonaldW. (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

The convergent trajectories of bird communities along ecological successions in european forests - Blondel, Jacques; Farré, H. (Oecologia, 1988)
There is much more variation in the composition of bird communities in the earlier open and semi-open seral stages of ecological successions in forested landscapes of Europe than later on in preforested and forested climactic stages. The demonstration of this trend is achieved from the study of four habitat gradients, two in the mediterra- nean region (Provence and Corsica) and two in central Eu- rope (Burgundy, France and Poland). A multivariate analy- sis has been used to illustrate the dynamics of communities along these successions. Displays of the results in bivariate space as well as an illustration of the distributional profiles of some of the most characteristic species show that: i) there is a discrimination between the two mediterranean gradients and the two medioeuropean ones and ii) each succession starts with a very distinct set of species and then the four gradients regularly converge in the last climactic stage where there is almost no discrimination between com- munities. These results are discussed in the light of the histo- ry of European biotas during the Pleistocene. The reason why there is more variation in species composition in the earlier seral stages than in the later forested stages are dis- cussed according to current theories on the role of habitat selection on speciation processes.
Keywords: Community dynamics; Ecological succession; historical biogeography; Mediterranean; speciation